Study of Spatial Distribution of Urban Amenities and Utilities and Its Effect on Settlement Patterns in Surakarta - Djaka Marwasta (Universitas Muhammadiyah Surakarta, 2004)
A study of spatial disttribution of urban failities and its impact on settlement pattern had been conducted. Southern part of Surakarta Municipality is chosen as study area. The aim was to study the correlation between spatial distribution of urban public facilities and settlement pattern. To obtain the settlement pattern and urban facilities distribution, manual photo interpretation and field survey method were used. The data were analyzed using geographi information system and statistical analysis tools. Map overlay module in the P Ar/ Info was used in order to join each variables of this research. To know the correlation between spatial distribution of urban facilities and settlement pattern, the multiple regression technique was used. The result shows that there was a positive signifiant relationship between urban public facilities distribution and settlement pattern. It means that the more distributed of urban publi facilities the better of settlement pattern (dense – uniform – large size building). Finally, condition of settlement pattern depends on how the goverment was able to manage the distribution of urban failities.